Neutrophil membrane camouflaged nanoprobes for NIR-II fluorescence imaging of inflamed, high-risk atherosclerotic plaques in mouse and rabbit models. (December 2022) - Jiang, Z.Z.; Geng, X.R.; Su, L.L.; Chen, A.N.; Sheng, Z.H.; Jiang, T.A.
Abstract: Atherosclerosis is the leading cause of vascular death worldwide, and inflammation plays a crucial role in atherosclerotic plaque progression and rupture. Fluorescent nanoprobes that can detect inflamed, high-risk atherosclerotic plaques and evaluate the therapeutic efficacy at the animal level in vivo are particularly meaningful. Herein, we developed a kind of neutrophil membrane-camouflaged nanoprobe in the second near-infrared spectral region (NIR-II) for the imaging of inflamed, high-risk atherosclerotic plaques in both mouse and rabbit models. Compared with free indocyanine green (ICG), the NIR-II fluorescence intensity of neutrophil biomimetic nanoparticles (Neu-NPs) was increased by 276% and had good stability in serum. Neu-NPs could specifically target inflamed, high-risk atherosclerotic plaques through the interaction of the chemokine receptor LFA-1with ICAM-1, which are highly expressed in inflamed sites. In the ApoE−/− mouse model, the signal-to background (S/B) ratio of the Neu-NP-treated mice was 1.67-fold higher than that of NP-treated mice. Even in large animals, such as the New Zealand white rabbit atherosclerosis model, Neu-NPs exhibited excellent targeting to high-risk atherosclerotic plaques. Moreover, the Neu-NPs could be used to reflect the reduction in plaque inflammation after the treatment and could thus be used for therapeutic evaluation and drug screening. Therefore, this highly biocompatible neutrophil membrane-camouflaged nanoprobe may be a new nanocarrier for the treatment of chronic inflammatory diseases such as atherosclerosis. Moreover, the use of NIR-II fluorescence imaging in mice and rabbits with atherosclerosis extends the scope of this emerging imaging technology. Highlights: Neutrophil membrane-camouflaged nanoparticles (Neu-NPs) targeting inflammation were fabricated. Neu-NPs exhibit a uniform size distribution and desirable biocompatibility. Neu-NPs could image inflamed plaques in both mice and rabbits in the second near-infrared spectral region. Neu-NPs could also dynamically monitor the changes in the degree of inflammation during treatment.